How Social Media Exposure to Health Information Influences Chinese People's Health Protective Behavior during Air Pollution: A Theory of Planned Behavior Perspective. Issue 3 (23rd February 2021) - Yang, Qinghua; Wu, Shiwen
ABSTRACT: Haze has become one of the most life-threatening problems in China and affects over one billion Chinese people's health. Chinese people have become more dependent on receiving health information from social media, especially Weibo and WeChat, which shapes their health perceptions and behaviors. To investigate how Chinese people's exposure to health information on social media influenced their health protective behaviors in response to haze, particularly wearing a PM2.5 anti-haze mask, we conducted a longitudinal web-based survey of mainland Chinese. The results from the structural equation modeling showed that (a) attitude and descriptive norm positively mediated the relationships between using Weibo for health information and behavioral intention while descriptive norm negatively mediated the relationship between using WeChat for health information and intention, and that (b) attitude, descriptive norm, and injunctive norm significantly predicted behavioral intention and wearing mask, but perceived behavior control did not. Theoretical and practical implications are discussed.